Effect of citrus sudden death on yield and quality of sweet orange cultivars in Brazil - Bassanezi, R. B.; Montesino, L. H.; Sanches, A. L.; Sposito, Maria Encarnação Beltrão [UNESP]; Stuchi, E. S.; Barbosa, J. C. (Amer Phytopathological Soc, 2007)
Citrus sudden death (CSD) has greatly affected sweet orange cultivars grafted on Rangpur lime in São Paulo and Minas Gerais States, Brazil. To characterize and quantify CSD damage, fruit yield and quality were assessed in each combination of sweet orange cultivar (Hamlin, Pera, Natal, and Valencia), age class (3 to 5, 6 to 10, and 11 to 15 years old), and CSD severity class (0 = no symptom, 1 = initial symptoms, and 2 = severe symptoms). For each combination, 10 trees were harvested and 20 fruit were taken for quality analysis. Damage was characterized by reduc_ tion of: (i) total weight of fruit/tree (36 and 67% for severity class 1 and 2, respectively), (ii) number of fruit/tree (27 and 55%), (iii) fruit size (13 and 25% in diameter and height [stem to styler distance]), (iv) fruit weight (32 and 56%), (v) total soluble solids (TSS)/fruit (18 and 42%), and increase of (vi) Brix (14 and 34%), (vii) acidity (16 and 41%), and (viii) TSS/90-1b. box (21 and 33%). There was no alteration on Brix/acidity ratio and percentage of juice on fruit of affected trees. Sweet orange cultivars did not differ in percentage of reduction or increase of all yield and quality variables, with the exception of Pera, which expressed increases of Brix and acidity. For more severe affected trees, the youngest plants showed a higher reduction in fruit number/tree, whereas plants 6 to 10 years old showed a higher increase in fruit acidity and TSS/box. However, no differences in percentage of reduction or increase for other variables were observed among different age classes. The damage to the above probably was associated with reduced water absorption capacity of CSD-affected trees.
Keywords: Citrus sinensis; C. limonia